Analysis of tax non-compliance in the trade sector. Model of risk management - Ramos Costilla, Johnny M. (2018)
This research analyzed the causes and effects of tax non-compliance in the commerce sector, and punctually to the evasion modality referred to the improper use of sales slips in the wholesale marketing of beer, soda, cosmetics, among other products. At the strategic level, a tax risk management model as a methodological tool is used of to facilitate the understanding of the causes, the formulation of corrective measures to the tax evasion modality analyzed, and the application of these measures in a timely manner and segmented based on the risk profile (behavioral position) of each taxpayer. This model is based on the practical application of theoretical bases related to the breach of the tax, raised by researchers from psychology, sociology and behavioral economics. Likewise, the model defines the institutional strategy and the operational actions that the Tax Administration must execute. At the operational level, the implementation of regulatory actions and operational management actions (facilitation and control actions) is formulated by the Tax Administration to correct the improper use of sales tickets in the wholesale trade sector.